Spectroscopic and Electrochemical Studies of Imogolite and Fe-Modified Imogolite Nanotubes - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Carbon nanotubes and other forms of carbon nanoparticles, as well as metal nanoparticles have been widely used in film electrochemistry because they allow for the immobilization of larger amounts of catalyst (either biological or inorganic) on the top of the modified electrodes. Nevertheless, those nanoparticles present high costs of synthesis and of separation and purification that hamper their employment. On the other hand, imogolites (Im), with the general formula (OH)3Al2O3SiOH, are naturally-occurring nanomaterials, which can be obtained from glassy volcanic ash soils and can also be synthesized at mild conditions. In this research paper, we characterize through spectroscopic techniques (i.e., fourier transform infrared spectroscopy (FTIR) spectroscopy, powder X-ray diffraction (XRD) and transmission electron microscopy (TEM)) synthetized Im and Fe-modified imogolite (Im(Fe)). Moreover, the Im and Im(Fe) were physically adsorbed on the top of a graphite electrode (GE) and were characterized electrochemically in the potential region ranging from 0.8 to 0.8 V vs. the saturated calomel electrode (SCE). When the film of the Im or of the Im(Fe) was present on the top of the electrode, the intensity of the charging/discharging current increased two-fold, but no redox activity in the absence of O2 could be appreciated. To show that Im and Im(Fe) could be used as support for catalysts, iron phthalocyanine (FePc) was adsorbed on the top of the Im or Im(Fe) film, and the electrocatalytic activity towards the O2 reduction was measured. In the presence of the Im, the measured electrocatalytic current for O2 reduction increased 30%, and the overpotential drastically decreased by almost 100 mV, proving that the Im can act as a good support for the electrocatalysts. © 2016 by the authors; licensee MDPI, Basel, Switzerland.